Pengembangan Model Aplikasi Simulator Kamera Video Berbasis Android Untuk Mata Kuliah Sinematografi Pembelajaran - Heri Triluqman; Mulyoto Mulyoto; Leo Agung Sutimin (Teknodika, 2018)
Integrating information and communication technology (ICT) in the learning process continues to evolve with various patterns and strategies, grouped into (1) e-Learning system, the process of learning that utilizes electronic devices and digital media, and (2) m- Learning, or mobile learning, the process of learning that utilizes mobile communication technology and devices. The rapid development of mobile devices, relatively easy operations, and more affordable prices, is a supporting factor in the widespread use of mobile learning to become a new alternative of learning media. These conditions encourage the formation of learning paradigm that can be done anytime and anywhere. The aim of the research is to develop the design/model of an Android-based Camcorder Simulator Application for the students of cinematography courses majoring education technology of education faculty in Semarang State University. This research method refers to the research and development (R&D) proposed by Borg and Gall (in Sukmadinata, 2016) with some modifications that have been developed by Sukmadinata. Withal, the research procedures used in this study focus on the development stages of application model/design. This step includes the following steps; (1) Model development (product design), (2) Design validation, and (3) Design revisions. The results of this study indicate that the process of developing an android-based camcorder simulator application model is done through the steps according to the research procedures, beginning with requirement analysis, then compiling competency map, material map, the main point of media content (GBIM), material descriptions (JM), flowchart and script, then design validation and product revision. Modeling camcoder simulator application is also ready for further stage of research and development. The use of an android-based camcorder simulator application is demanded in the learning process of cinematography course, especially the engineering material and the shooting procedure as it can assist students to be autonomous learners.